(untitled) (Research, Society and Development, 2021)
With the advent of the new pandemic for the new Coronavirus, a reason for worldwide confrontation by professional nurses on the front lines has raised concerns about the organization of health services. In view of the scenario, the need to contextualize the coping with chronic acute respiratory diseases is one of the concerns. Thus, this study aims to report the role of nurses in the organization of health services during the pandemic of COVID-19. With this perspective, a descriptive study, with a qualitative approach, of the experience report type, was carried out on the role of nurses in the organization of the health service during the pandemic of COVID-19. With the emergence of the need to re-adapt services for welcoming and tracing suspected cases and implementing Units for Flu Syndromes, nurses were placed as protagonists in health services in the management and provision of frontline care in the Pandemic scenario. In this sense, health services now receive a different managerial guise for the cases of SARV-CoV-2 attended and observed. These conditions emerge for the challenges of thinking about the role of nurses in the management of health services. In this scenario of the pandemic, basing the knowledge in the face of the emergency responses for the development of cases of infection by COVID-19, the role of the nurse represents the change in the performance of managers and health professionals who struggle daily for the improvement and quality of the assistance provided the population.